Исследования Чугуевского городища в 2009 г. - Свистун, Г.Е. (Археологічні дослідження в Україні, 2010)
The main results of the works of the Siverskyi Donets Archaeological Expedition of the I.Ye. Repin Artistic and Memorial Museum and of the State Enterprise Protective Archaeological Service of Ukraine of the IA NASU «Slobidska Archaeo logical Service» at Chuhuiv hill-fort in 2009 are presented. Layers of Saltovo-Mayak culture from the middle of the 8th c. to the beginning of the 10th c.; of the Late Mediaeval period, the time of active settlement of Sloboda Ukraine in the second half of the 17th c. and the 18th c., and of the military settlement of the first half of the 19th c. were studied. Dwelling, husbandry, and public complexes were discovered, as well as numerous finds of the listed periods.